B2 Abilities In Bilingual Speech of 6th Grade Students of State Elementary School 83 Ternate City - Tualeka, Erwin; Arbain, Rukmin; Rusly, Nasrullah (International Journal of Education, Information Technology, and Others, 2025)
This study is a qualitative study that aims to identify the bilingualism abilities of 6th grade elementary school children by observing the B1 and B2 sentence patterns, and the code-mixing phenomenon spoken by the bilinguals. This study uses a qualitative descriptive method, data collection using the listening method with recording and note-taking techniques then data analysis using content analysis. The results of the study consisting of 70 data, found that the B1 and B2 speech of 6th grade elementary school children had met the standards of good sentences. However, several grammatical errors were found, including the incorrect placement of conjunctions, then in the utterance of B2/Indonesian sentences, 4 data were found to contain code-mixing while the B1 data did not find any form of Ternate Malay code-mixing, so it can be concluded that mastery of B1 is better than mastery of B2.